Strike-slip and tectonics granitoid emplacement: an AMS fabric study from the Odenwald Crystalline Complex, SW Germany - Greiling, Reinhard O.; Verma, Pramod Kumar (Mineralogy and petrology, 2001)
AMS fabric studies supported by field and microscopic work were applied to identify the internal structure and possible emplacement processes of the Variscan late-tectonic granodiorite-granite intrusions of the Unit III in the Odenwald Crystalline Complex. This Unit is bounded towards NW and NNE by steeply inclined shear zones, the southern part is unexposed. The magnetic susceptibility ranges between 10−3 and 10−6 SI units and is caused by paramagnetic and subordinately by ferromagnetic components. AMS ellipsoids are typically oblate with gently plunging long axes (lineations). AMS foliations and lineations trend mainly WSW-ENE and NNW-SSE, parallel with the NNW and ENE trending marginal shear zones of Unit III, respectively. As revealed by microstructural studies, a penetrative foliation in the plutons is related to emplacement processes. Therefore the observed AMS foliation and lineation are also interpreted as the result of syn-emplacement deformation which is dominantly strike-slip. Weakly inclined foliations around pluton roof xenoliths point to a component of buoyant rise of magma. It is suggested that the granitoid magma was generated in a low level anatectic zone along a left-lateral transpressive shear zone during local extension at releasing bends. During successive fault movements magma ascended through extensional parts of the shear zone. Local normal faults and the Otzberg zone at the eastern margin of Unit III document mostly brittle extension, which overprinted the strike-slip fabrics after the emplacement of the plutons.